UNCLOS' Role and Limitations in Resolving Marine Territorial Disputes: Integrating Islamic Jurisprudence for Enhanced Effectiveness - Ali, Saleh Hussain; Resen, Sami Hammadi; Subhi, Anas Akram Mohammed; AlShaeer, Mahmood Jawad Abu-; Chornomordenko, Ivan (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
The article critically examines the United Nations Convention on the Law of the Sea (UNCLOS) and its limitations in addressing marine territorial disputes, especially in regions where Islamic jurisprudence holds influence. Given the strategic and resource value of marine territories, international conflicts frequently arise over these areas. While UNCLOS aims to regulate and resolve such disputes, its effectiveness is hindered by geopolitical power dynamics and enforcement challenges. This research utilizes a mixed-methods approach, involving an extensive review of historical conflicts governed by UNCLOS, along with qualitative interviews with diplomats, international law experts, and Islamic legal scholars. Findings reveal that while UNCLOS establishes a formal legal framework for marine claims, its application often falls short in regions where political interests supersede legal protocols. Integrating principles of Islamic jurisprudence, particularly justice, equity, and mutual respect, can offer alternative pathways to enhance UNCLOS's efficacy in dispute resolution. The article concludes that incorporating Islamic legal principles could address UNCLOS’s shortcomings, fostering a more harmonious and cooperative maritime environment in geopolitically sensitive areas.